A Genome-Wide Investigation of Effects of Aberrant DNA Methylation on the Usage of Alternative Promoters in Hepatocellular Carcinoma - Dong, Yuting; Liu, Xiaozhao; Jiang, Bijun; Wei, Siting; Xiang, Bangde; Liao, Ruichu; Wang, Qiuyan; He, Ximiao (Frontiers in Oncology, 2022)
Background: The alternative usage of promoters provides a way to regulate the gene expression and has a significant influence on the transcriptome and contributes to the cellular transformation of cancer. However, the function of alternative promoters (APs) in hepatocellular carcinoma (HCC) has not been systematically studied yet. In addition, the potential mechanism of regulation to the usage of APs remains unclear. DNA methylation, one of the most aberrant epigenetic modifications in cancers, is known to regulate transcriptional activity. Whether DNA methylation regulates the usage of APs needs to be explored. Here we aim to investigate the effects of DNA methylation on usage of APs in HCC. Methods: Promoter activities were calculated based on RNA-seq data. Functional enrichment analysis was implemented to conduct GO terms. Correlation tests were used to detect the correlation between promoter activity and methylation status. LASSO regression model was used to generate a diagnostic model. Kaplan-Meier analysis was used to compare the overall survival between high and low methylation groups. RNA-seq and whole-genome sulfite sequencing (WGBS) of HCC samples were performed to validate the correlation of promoter activity and methylation. Results: We totally identified 855 APs, which could be well used to distinguish cancer from normal samples. The correlation of promoter activity and DNA methylation in APs was observed, and the APs with negative correlation were defined as methylation-regulated APs (mrAPs). Six mrAPs were identified to generate a diagnostic model with good performance (AUC = 0.97). Notably, the majority of mrAPs had CpG sites that could be used to predict clinical outcomes by methylation status. Finally, we verified 85.6% of promoter activity variation and 92.3% of methylation changes in our paired RNA-seq and WGBS samples respectively. And the negative correlation between promoter activity and methylation status was further confirmed in our HCC samples. Conclusion: The aberrant methylation status plays a critical role in the precision usage of alternative promoters in HCC, which sheds light on the mechanism of cancer development and provides a new sight of cancer screening and treatment.